Green marketing: Importance in the adoption of the electric cars in the portuguese market - Ferreira, Rita Maria Machado (My University, 2022)
The present dissertation aims to scrutinise and conceive to what extent green marketing has a positive or negative impact on adopting electric cars in Portugal. With the growing emergence of environmental concerns and the consequent pursuit of sustainability, electric vehicles have been resurgent over the last two decades, at a global level. Considering this fact, it becomes relevant to study and understand the motivations of consumers of these vehicles, namely the issues of environmental impact and sustainability of electric cars. Regarding the methodology, a quantitative method is used to test hypotheses relevant to the topic. In this sense, it was essential to carry out an online survey to collect data on this matter, which made it possible to generate a sample of 317 people in Portugal. Findings revealed that environmental impact influences the adoption of electric cars in Portugal. These results contribute to the existing literature on the importance of environmental factors for consumers when planning to adopt these cars. It can also help Portuguese companies to better define their marketing strategies through the practice of green marketing to this target audience.
Keywords: Electric cars; Green marketing; Environmental impact